Style and Function of Humor in the Animation Series ’Tekotok’ as a Form of Social Criticism - Rokhmah, Akhirul Insan Nur; Suwandi, Sarwiji; Setiawan, Budhi (Advances in Social Sciences Research Journal, 2024)
Our lives cannot be separated from the existence of humor. Humor developed into several theories. This research aims to describe and classify Tekotok animated humor based on Aaker and Bagdonas’ theory. There are 4 styles of humor in Tekotok animation, namely the standup, sweetheart, the magnet, and the sniper humor styles. The dominant humor style still uses the Stand-Up humor style. The function of humor is to relieve tension, as a ritual, as social control, and as a social bond. This research used descriptive-qualitative methods. The rest is additional data such as documents and others. The theory used is content analysis theory. Data collection was carried out using random purposive sampling. Sampling was carried out in accordance with the requirements, that the research object must contain the phenomenon of social issues.